Cutaneous Malignant Melanoma in Chile: Differences in Tumor Thickness and Overall Survival Between Patients From Public and Private Health Care Centers - Martínez, Guisella; Bobadilla, Francisco; Kinzel, Francisca; Fernández, Javier; Sazunic, Ivo; Delgado, María Magdalena; Segovia, Laura; Zamudio, Andrea; Vega, Nadia (Dermatology Practical & Conceptual, 2023)
Introduction: A low socioeconomic status (SES) is associated with lower survival rates in cutaneous malignant melanoma (CMM). In South America, there are few studies that analyze CMM data according to SES.Objectives: To determine the differences in microstaging and overall survival in CMM between public and private health care centers.Methods: Retrospective cohort study. Histopathological reports with a diagnosis of CMM from two public hospitals (PuH) and one private health care center (PrH) in Santiago from 2008 to 2018 were included. Patients’ death certificates were obtained to estimate overall survival.Results: 1014 MMC were found. The mean age was 58.6 ± 16.8 years and 59.9% corresponded to female patients. Of these, 33.9% received treatment at PuH and 66.1% at PrH. Patients from PuH had an increased risk of having an invasive CMM and a >1 mm thickness melanoma compared to PrH (OR 2.77 and 6.06, respectively). Patients with invasive CMM from the PuH were 6.29-fold more likely to die than a patient from the PrH.Conclusions: We observed a great disparity in tumor thickness between the socioeconomic sectors, reflecting a later detection and lower survival rate in PuH. Our results highlight a gap on which National Public Health should focus.